1999
DOI: 10.1530/eje.0.1400029
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of GH therapy in GH-deficient children treated before 1 year of age

Abstract: Objectives: To evaluate the long-term effects of GH therapy in early diagnosed GH-deficient patients treated before 1 year of age. Study design: We studied all 59 patients (33 males) recorded by Association France-Hypophyse and treated with GH (0.50 Ϯ 0.15 IU/kg (S.D.) per week) before 1 year of age. Clinical presentation and growth parameters under GH treatment were analyzed. Results: Neonatal manifestations of hypopituitarism were frequent: hypoglycemia (n ¼ 50), jaundice (n ¼ 25) and micropenis (n ¼ 17/33).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 23 publications
(31 reference statements)
5
34
1
1
Order By: Relevance
“…In conclusion, our 7-year prospective study on GHD infants treated with GH from less than two years of age has confirmed the conclusions of other recent prospective (11) and retrospective (12)(13)(14)(15) treatment of GHD in childhood. Moreover it has demonstrated that the influence of BW on growth response to GH therapy in GHD children persists over time, at least when treatment is begun from less than two years of age.…”
Section: Discussionsupporting
confidence: 88%
“…In conclusion, our 7-year prospective study on GHD infants treated with GH from less than two years of age has confirmed the conclusions of other recent prospective (11) and retrospective (12)(13)(14)(15) treatment of GHD in childhood. Moreover it has demonstrated that the influence of BW on growth response to GH therapy in GHD children persists over time, at least when treatment is begun from less than two years of age.…”
Section: Discussionsupporting
confidence: 88%
“…In the past few years, there have been a few studies reporting long-term growth results after rGH therapy in early-treated GH-deficient patients [26, 27, 28, 29], but only one report on AH has been published [30]. In this report, we were able to confirm that early GH replacement therapy produced a normal and target-related AH in a group of patients with idiopathic GHD (fig.…”
Section: Ah Of Patients With Ghd Treated With Rgh Since the First Yeasupporting
confidence: 60%
“…After infancy, the nutritional component of IGF-1-dependent growth is gradually replaced by GH stimulation on IGF-1 synthesis (20,27). During childhood, boys with CHH experienced relatively normal childhood growth.…”
Section: Discussionmentioning
confidence: 99%